Spatial epidemiology of american cutaneous leishmaniasis in a municipality of west são paulo state, brazil - Da Fonseca, Elivelton Silva; Dandrea, Lourdes A. Zampieri; Taniguchi, Helena Hilomi; Hiramoto, Roberto Mitsuyoshi; Tolezano, José Eduardo; Guimarães, Raul Borges (My University, 2014)
Background & objectives: In the last decade, in the state of São Paulo, 5898 cases of cutaneous leishmaniasis (CL) were reported. This study was undertaken to analyze the epidemiology of CL in the municipality of Teodoro Sampaio, in São Paulo State, Brazil, based on a geographic approach, as very little is known of the relationship between CL and the spatial transformation process. Methods: This is a population-based quantitative, descriptive and cross-sectional case study. Surveys of the official notifications in the healthcare center and official sources from 1998 to 2011 were analysed. The data were described based on statistics and the Kernel method to detect hotspots of transmission. Results: The age group between 21 and 40 yr was most affected, with 24 cases (57.9%). Of the 41 cases reported between 1998 and 2011, 33 cases were having low education status and 31 cases (75.6%) were males. The spatial and temporal distribution was aggregated in three-year periods which permitted the identification of two microfoci, in periods I (1998–2000) and III (2005–2007). Interpretation & conclusion: The disease has presented, in recent years, a pattern of sporadic transmission or microfoci, and continues to maintain enzootic cycles of Leishmania in a sylvatic environment, ensuring the perpetuation of the pathogen in nature, and the risk of emergence of new cases of CL in domestic animals and humans.
Keywords: Brazil; Cutaneous leishmaniasis; Spatial analysis; São Paulo state